Possible germline progenitor cells in extra-gonadal tissues of the sea anemone, Exaiptasia diaphana - Shao, Pei-Jung; Chiu, Yi-Ling; Tsai, Pin-Hsuan; Shikina, Shinya (Frontiers in Marine Science, 2023)
Many anthozoans, e.g., sea anemones and corals, have remarkable capacities for asexual reproduction and regeneration, creating complete individual polyps from pieces of parental polyp tissue. Notably, polyps produced asexually (or regenerated) from somatic tissues that originally contain no gonads are capable of sexual reproduction. However, how somatically derived polyps can reproduce remains largely unexplored. Here, using a sea anemone, Exaiptasia diaphana, we show that potential germline progenitor cells are present in the extra-gonadal tissues, and that they are allocated to newly produced individuals during asexual reproduction/regeneration. Histological analysis of E. diaphana demonstrated that polyps asexually produced from pedal lacerates can create mature gametes. Amputation experiments showed that polyps regenerated from the head, which originally lacked gonadal tissue, formed gonads and initiated gametogenesis. Immunohistochemical analysis with a germline marker, vasa, demonstrated the presence of vasa-positive cells in various polyp tissues. These findings suggest that vasa-positive cells in extra-gonadal tissues may be a reservoir of germline progenitor cells to ensure sexual reproductive capacity in individuals produced asexually or regenerated from somatic tissues.